Why Training in Ecological Research Must Incorporate Ethics Education. Issue 5 (September 2015) - Crozier, G.K.D.; Schulte‐Hostedde, Albrecht I.
Abstract Like other science, technology, engineering, and mathematics fields, ecological research needs ethics. Given the rapid pace of technological developments and social change, it is important for scientists to have the vocabulary and critical‐thinking skills necessary to identify, analyze, and communicate the ethical issues generated by the research and practices within their fields of specialization. The goal of introducing ethics education for ecological researchers would be to promote a discipline in which scientists are willing and able to engage in ethical questions and problem solving, even if they do so inadequately at first. Practicing ecologists ought to be able to identify and critically evaluate the ethical dimensions of their field studies because ecologists are at the forefront of important interfaces between humans and other‐than‐human organisms and natural systems. They are among the first to identify the impact of anthropogenic changes to the environments. Rapidly changing local and global environments mean that ecologists will be on the front line of any efforts to create a sustainable lifestyle for humans on this planet.